Circulating MicroRNAs are Promising Novel Biomarkers of Acute Myocardial Infarction - Zhang, Yinhui; Wang, Rongrong; Pu, Jielin; Li, Ning; Ran, Yuqin (Internal Medicine, 2011)
Objective Recent studies have revealed that microRNAs (miRNAs) are involved in the regulation of cardiac development, physiologic, and pathologic processes via post-transcriptional control of gene expression. The stable circulating miRNAs offer unique opportunities for the early diagnosis of several diseases. In this study, we examined the circulating miR-133 and miR-328 levels from patients with acute myocardial infarction (AMI). Patients and Methods Twenty-eight control subjects and fifty-one consecutive AMI patients were enrolled. The plasma and whole blood samples from AMI patients were obtained within 24 hours (n=51) and 7 days (n=6) after the onset of AMI symptoms. The circulating miR-133 and miR-328 levels were analyzed using quantitative real-time PCR. Results The miR-133 levels in plasma from AMI patients exhibited a 4.4-fold increase compared with control subjects (p=0.006). Moreover, the increased miR-133 levels in whole blood were comparable with those in plasma samples. In contrast, the miR-328 levels in plasma and whole blood of AMI patients were markedly increased by 10.9-fold and 16.1-fold, respectively, compared to those in control subjects (p=0.033 and p<0.001). The elevated circulating miR-133 and miR-328 levels were recovered to the control levels at 7 days after AMI. In addition, there was a correlation between circulating miR-133 or miR-328 levels and cardiac troponin I. Furthermore, circulating miR-133 or miR-328 showed no significant changes in AMI patients with tachyarrhythmia (n=24) or bradyarrhythmia (n=26) compared to those in patients without arrhythmias. Receiver operating characteristic curve analysis revealed that the areas under the curve of miR-133 or miR-328 in plasma and whole blood were 0.890, 0.702 and 0.810, 0.872, respectively (all p<0.05). Conclusion The miR-133 and miR-328 levels in plasma and whole blood in AMI patients were increased compared to those in control subjects. These miRNAs may represent novel biomarkers of AMI.